Process tomography : principles, techniques, and applications - Williams, R. A. (Richard Andrew), 1960-; Beck, M. S. (Maurice S.) (Butterworth-Heinemann, 1995)
Written by international experts in this field, the book describes the principles of, and presents case studies for, the wide range of tomographic imaging techniques that can be used in the process industries. It includes sufficient introductory material to this multi-disciplinary subject in order that readers from a variety of backgrounds will be able to fully understand the fundamental principles and features of the sensors and image reconstruction techniques needed for process tomography.